Optical characterization of molybdenum disulfide by raman and photoluminescence - Sun, Linfeng (2016)
In this thesis, Raman and PL spectroscopy of MoS2 layers are investigated. It could be divided into three parts: (1) The resonant Raman spectra in few layer MoS2 are observed when samples excited by 325 nm laser. The significance of this work is to determine the value of SO splitting in single layer MoS2 experimentally; (2) The origin of strong PL spectra of CVD grown single layer MoS2 are investigated by comparing the PL spectra of CVD grown and ME smaples. Combined with the first principles calculations, this work reveals the intrinsic reason for the abnormally strong PL intensity in CVD grown MoS2. This work guides us a way to engineer MoS2 layers for its potential application in light emitting devices; (3) MoS2 nanosheets are used as the substrate of surface enhanced Raman scattering in this work. The defects introduced during the plasma treatment in MoS2 nanosheets are helpful to enhance the Raman signal of detected analytes. In summary, this work introduces the fundamental properties of MoS2 layers by Raman and PL spectroscopy and investigates its potential applications on electronics, biosensors and so on.